KETAHANAN PANGAN MASYARAKAT PERLADANGAN DI KABUPATEN BARITO UTARA (STUDI KASUS KECAMATAN GUNUNG TIMANG) - Eti Dewi Nopembereni (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
Food problems include food availability, distribution and food consumption, and become a history of Indonesian nation-building, where food security is closely related to economic stability. The aim of this study; Identify and describe how to obtain and process foodstuffs by shifting cultivation. The research method was determining the location purposively, Gunung Timang Subdistrict, taking 50 samples by simple random sampling, taking data through observation and interviews, then the data were analyzed qualitatively. The results of the study, local communities as shifting cultivators, are accustomed to diversifying the types of plants managed on land, namely upland rice, tubers, vegetables, fruits, and native chicken and duck / duck livestock, while protein (meat) is generally obtained by hunting methods (birds, squirrels, wild boar, etc.). The Central Kalimantan region is also famous for its many large and small rivers, including mountain water sources, so that for protein needs it is also obtained from river fish (freshwater fish).